Comparison of Glucose and Lipid Metabolic Gene Expressions between Fat and Lean Lines of Rainbow Trout after a Glucose Load - Jin, Junyan (Public Library of Science, 2014)
Two experimental rainbow trout lines developed through divergent selection for low (Lean ‘L’ line) or high (Fat ‘F’ line) muscle fat content were used as models to study the genetic determinism of fat depots. Previous nutritional studies suggested that the F line had a better capability to use glucose than the L line during feeding trials. Based on that, we put forward the hypothesis that F line has a greater metabolic ability to clear a glucose load effectively, compared to L line. In order to test this hypothesis, 250 mg/kg glucose was intraperitoneally injected to the two rainbow trout lines fasted for 48 h. Hyperglycemia was observed after glucose treatment in both lines without affecting the phosphorylation of AMPK (cellular energy sensor) and Akt-TOR (insulin signaling) components. Liver glucokinase and glucose-6-phosphate dehydrogenase expression levels were increased by glucose, whereas mRNA levels of β-oxidation enzymes (CPT1a, CPT1b, HOAD and ACO) were down-regulated in the white skeletal muscle of both lines. Regarding the genotype effect, concordant with normoglycemia at 12 h after glucose treatment, higher muscle glycogen was found in F line compared to L line which exhibited hyperglycemia. Moreover, mRNA levels of hepatic glycolytic enzymes (GK, 6PFK and PK), gluconeogenic enzyme PEPCK and muscle fatty acid oxidation enzymes (CPT1a, CPT1b and HOAD) were concurrently higher in the F line. Overall, these findings suggest that F line may have a better ability to maintain glucose homeostasis than L line.